1993
DOI: 10.1103/physrevlett.70.790
|View full text |Cite
|
Sign up to set email alerts
|

Attainment of space-charge dominated beams in a synchrotron

Abstract: For a given rf cavity voltage, there is a maximum attainable peak current in an ion storage ring. This occurs when the electric field from the beam space charge is balanced by the field from the rf cavity. In this limit, the linear charge density distribution is parabolic and incoherent synchrotron motion is suppressed. The beam energy spread cannot be determined from the bunch length which depends only on the beam current and rf voltage. This has been observed using the high energy electron-cooling system at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…In Ref. [13] it was shown that for a modulated rf phase the response of the synchrotron motion in a single rf wave shows characteristics of chaotic particle dynamics in a parametric resonant system. The importance of these findings for the collective response of bunches affected by space charge is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [13] it was shown that for a modulated rf phase the response of the synchrotron motion in a single rf wave shows characteristics of chaotic particle dynamics in a parametric resonant system. The importance of these findings for the collective response of bunches affected by space charge is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…No ions are lost at this point although the Schottky-signal appears to be considerably weaker, as the integrated pick-up signal (not shown) remains constant. Furthermore, the measured bunch length can be reproduced under the assumption of space charge dominated bunches within 10% [16].…”
Section: Laser Cooling Of Li-like Carbon Ionsmentioning
confidence: 95%
“…The CEBAF FEL injector beam dynamics shows large space-charge effects, even at 10 MeV (γ ≈ 20). 1 Space-charge dominated longitudinal motion has also been studied in the IUCF ion storage ring 2,3 . Previously a longitudinal envelope equation with a selfconsistent phase-space distribution has been developed, 4 and has been of considerable use in analyzing the motion of these cases.…”
Section: Introductionmentioning
confidence: 99%